Experimental Setup for Measuring the Effect of Biofilm Build-up on Heat Transfer in Drinking Water Pipes - Konstantinos Glynis; Mirjam Blokker; Zoran Kapelan; Dragan Savić (Engineering proceedings, 2024)
Biofilm formation in drinking water distribution systems (DWDSs) poses challenges to water quality and system integrity. Traditional measurement methods often involve intrusive techniques, disrupting the biofilm ecosystem, while non-intrusive methods offer promising alternatives. This paper explores the feasibility of using non-intrusive temperature sensing to monitor biofilm growth in PVC pipes. Through experiments using the SLIMER 2.0 setup, the biofilm accumulation’s impact on the heat transfer properties is investigated. Preliminary results show successful biofilm growth under controlled conditions, with temperature measurements revealing alterations in heat resistance, hence providing a basis for biofilm monitoring. This study contributes to advancing biofilm monitoring techniques, offering insights for improved water quality management in DWDSs.